Occurrence of Cystacanths of Pomphorhynchus laevis (Zoega in Muller, 1776) (Acanthocephala) in its Intermediate Host Gammarus obnixus Karaman & Pinkster, 1977 (Am phipoda): A Comparative Study - (:unkn) unknown (INST ZOOLOGY, BAS, 2020)
The amphipod Gammarus obnixus Karaman & Pinkster, 1977 is an intermediate host for the acanthocephalan parasite Pomphorhynchus laevis (Zoega in Muller, 1776). Specimens of G. obnixus were collected from two sampling stations: (1) Isikh Spring (clear, cold water with a fast current and hard substratum with a gravel-covered bottom) and (2) a rainbow trout net-cage area (dense community of macrophytes on a soft substratum due to net-cages residues and high water turbidity). The aim of this study was to determine monthly changes of the larval occurrence of P. laevis and to understand the effect of the fish fanning on the infection rate with cystacanths of P. laevis. A total of 14,027 specimens of G. obnixus were collected. Cystacanths of P. laevis were found in the hemococl of the gammarids. At the Isikli Spring, P. laevis infected 832 (16.2%) of the 5149 G. obnixus examined over the total sampling period and had a mean intensity of the cystacanths of 1.5 and mean abundance 0.2 per amphipod individual. At the netcage area, P. laevis infected 3480 (39.2%) of the 8878 G. obnixus, with a mean intensity of 2.3 and mean abundance 0.9 per amphipod host. Amphipods in all 12 length classes were infected with P laevis. The maximum intensity of the infection was 16 cystacanths of P. laevis in a single G. obnixus in August. Sex ratio of the cystacanths was approximately 1:1. Males of G. obnixus from both stations were more heavily infected than females. The results showed that the population density and infection rates of G. obnixus were higher at the net-cage area than at the Isikli Spring.
Keywords: Cystacanths; Pomphorhynchus laevis; intermediate host; Gammarus obnixus; ECHINOGAMMARUS-STAMMERI; PARASITE; AMPHIPODA; BEHAVIOR; CRUSTACEA; CIVRIL; PULEX